Analisis Harga Pokok Produksi dan Harga Jual Kasur dengan Metode Full Costing - Noviyanti Noviyanti (Jurnal Akuntansi Keuangan dan Bisnis, 2024)
The purpose of research at PT Cahaya Mitra Utama is to calculate the cost of production using the full costing method and determine the selling price which affects the amount of profit recognized by the company. This research uses a type of case study research with a descriptive approach and data collection methods, namely the method of observation, literature study, interviews as well as document collection. The data analysis technique used is qualitative and quantitative data analysis techniques. The results of the study concluded that there was a difference in production costs by company of Rp 1.352.640.000 while according to the author Rp 1.399.766.666. The difference in factory overhead costs from the company’s calculations is Rp 18.600.000 and the author’s calculation is Rp 71.966.666, with the final result of the difference in the total selling price between company methods of Rp 1.623.168.000 and the selling price according to the author’s calculations is Rp 1.679.720.000. This occurs after classifying costs and calculating costs according to cost accounting concepts. Therefore, the calculation of the cost of production and selling prices can be determined precisely.